Integrated Quality Management and Nurse Job Satisfaction: Unveiling the Non-Linear Relationship - Dardin, Dardin; Huriati, Huriati; Arbianingsih, Arbianingsih; Anwar, Mulyana (Journal Nursing Care Jurusan Keperawatan Politeknik Kesehatan Gorontalo, 2025)
Background: Job satisfaction is an essential aspect in hospitals that can increase the productivity of services. In achieving a good hospital image, minimizing negative perceptions of the hospital is necessary. However, the problem that often arises in human resource management is finding the best way to achieve employee job satisfaction.Purpose: This study aims to determine the relationship between integrated quality management and the job satisfaction of nurses in hospitals.Methods: This study uses a quantitative research design with a cross-sectional study approach. The sampling technique uses Purposive sampling. The sample obtained was 144 respondents. Sampling using a questionnaire. Data analysis using Pearson correlation.Results: The results of this study found that there was no significant relationship between integrated quality management and nurse job satisfaction. Many factors influence nurse job satisfaction.Conclusion: Integrated quality management does not directly affect nurses’ job satisfaction but is mediated through other variables.